’n Christelik Psigo-opvoedkundige Perspektief op die Algemene Vaardighede en Tegnieke van Neuro-linguïstiese Programmering - Vorster, C. M.; du Plooy, J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
It is maintained that the Neuro-linguistic Programming model (NLP) does not merely consist of a set of techniques that are used in isolation, but that all the NLP components, both the skills and the techniques, must be viewed holistically. The NLP-techniques can be divided into NLP communication techniques and NLP esoteric techniques. Because most of the NLP techniques have elements of both categories, it is difficult to draw a definite line between these two categories. Some of the NLP skills are occasionally regarded as communication techniques. Following the discussion in this article of the most important NLP skills and techniques, attention will be given to the value of the application of these skills and techniques for psycho-education from the perspective of a Christian scientist. The authors of this article have reached the conclusion that Christian scientists should not support and apply the NLP.